“MORTE DAS CASAS DE OURO PRETO”: UMA VISADA ARQUITETÔNICA - Dall'Alba, Eduardo (Organon, 2012)
The making of the poem Morte das casas de Ouro Preto (The death ofOuro Preto houses), by Carlos Drummond de Andrade about the idea of planningand imagining, perceptible data of the poetic construction. It is a study that investigatesthe thematic and formal structure of this Drummond´s poem.